Online Obstetrics and Gynecology Medical Students Clerkship During the Covid-19 Pandemic: a Pilot Study - Armon, Shunit (Med Sci Educ, 2021)
BACKGROUND: The Covid-19 pandemic and social distancing resulted in the need for an immediate transition of all medical education to online education with a concern that such a pandemic might recur. OBJECTIVE: To assess the feasibility of an online clinical rotation in Obstetrics and Gynecology during the Covid-19 pandemic and to identify effective pedagogical modalities as well as obstacles to online learning. METHODS: A questionnaire was sent to the students and staff at the end of the 3-week online rotation. The online curriculum included synchronous learning such as problem-based learning, video demonstrations and discussions, as well as asynchronous pre-recorded lectures. Questions addressed expectations, previous experience, difficulties encountered, effectiveness of different types of pedagogy, and willingness to participate in online education in the future. RESULTS: We received 27 completed questionnaires, 77% response rate. Overall course rating was 4.14/5 from the students and 3.38/5 from the staff. Previous experience in online education had a positive correlation with higher overall course evaluations; however, low expectations of effectiveness of online learning prior to the course did not correlate with the overall course rate. Challenges identified were absence of bedside teaching and lack of feedback. Effective pedagogical modules were problem-based learning and videos. Additionally, 72% stated that online learning should be part of the formal curriculum. CONCLUSION: Further research into tele-teaching should be part of medical school strategic plan to ensure meaningful learning in these emerging modalities not limited to exceptional situations such as pandemics. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s40670-020-01181-y.